2006
DOI: 10.1590/s1806-37132006000300010
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da reação em cadeia da polimerase no diagnóstico da tuberculose pulmonar em pacientes indígenas e não indígenas

Abstract: Positivity and isolation of nontuberculous mycobacteria in the acid-fast smear in conjunction with polymerase chain reaction positivity raise the following hypotheses: nontuberculous mycobacteria species with DNA regions homologous to, or even still possessing, the M. tuberculosis IS6110 exist in the Amazon; colonization of the oropharynx or of a tuberculous lesion accelerates the growth of the nontuberculous mycobacteria present in the sputum samples, making it impossible to isolate M. tuberculosis; A history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…According to some authors, fungi and bacteria from these sites can affect the results of PCR from sputum. 16 However, others have reported high PCR sensitivity and specificity for tuberculosis diagnosis, despite the fact that the samples were clearly contaminated with these microorganisms. 17 In our study, we utilized only one sample for the same sputum.…”
Section: Discussionmentioning
confidence: 99%
“…According to some authors, fungi and bacteria from these sites can affect the results of PCR from sputum. 16 However, others have reported high PCR sensitivity and specificity for tuberculosis diagnosis, despite the fact that the samples were clearly contaminated with these microorganisms. 17 In our study, we utilized only one sample for the same sputum.…”
Section: Discussionmentioning
confidence: 99%
“…Barreto and Campos (2000) found 35 patients with NTM and showed that isolates of the M. avium complex, M. terrae and M. fortuitum were most common in samples collected between 1994 and 1999 in North of Brazil. A study that evaluated respiratory samples of non-indigenous and indigenous patients from Amazonas State with suspected pulmonary TB identified 19 patients with NTM infection, but the study did not report the identity of the isolates at the species level (Santos et al, 2006 Zamarioli et al 2008;Pedro et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…e colonização da lesão cutânea, visto que existe o relato da presença de várias espécies de micobactérias na flora da pele normal de pessoas residentes no estado do Amazonas (19,20) ; a existência, na Amazônia, de espécies de MNT contendo a IS6110, conforme também relatado por Santos et al (18) ; ou a uma homologia entre o DNA destas MNTs e a IS6110, semelhante ao exposto por outros autores (3,11,15) . Visto que em quatro amostras o problema parece estar relacionado com o impedimento de desenvolvimento do M. tuberculosis, a falsa-positividade foi de 9,5% para todos os casos.…”
Section: Tabela 2 Tabelaunclassified